A Highly Efficient and Durable Kirigami Triboelectric Nanogenerator for Rotational Energy Harvesting - Kong, Dae Sol; Han, Jae Yeon; Ko, Young Joon; Park, Sang Hyeok; Lee, Minbaek; Jung, Jong Hoon (Energies (Basel), 2021)
While sliding-mode triboelectric nanogenerators (S-TENGs) have been considered as one of the most promising devices for rotational energy harvesting, their inherently poor durability has been a serious bottleneck for applications. Herein, we report a three-dimensional kirigami TENG as a highly efficient and durable rotational energy harvesting device. The kirigami TENG consisted of cube-shaped paper, aluminum (Al) foil electrode and polytetrafluoroethylene (PTFE) polymer film, and converted rotational motion into multiple folding-unfolding vibrations. The rotation-folding (R-F) kirigami TENG generated an open-circuit voltage of 31 V, a short-circuit current of 0.67 μA and an instantaneous power (power density) of 1.2 μW (0.13 μW/cm2) at 200 rpm, which was sufficient to turn on 25 light-emitting diodes and a thermo-hygrometer. The triboelectric outputs of the R-F kirigami TENG were only slightly decreased even after 288,000 continuous rotations, i.e., the output remained at 86% of its initial value. This work demonstrates that an R-F kirigami TENG could be a plausible candidate to efficiently harvest various forms of rotational energy with a long-term durability.